Empowering smart grid: A comprehensive review of energy storage technology and application with renewable energy integration - Tan K.M.; Babu T.S.; Ramachandaramurthy V.K.; Kasinathan P.; Solanki S.G.; Raveendran S.K. (Elsevier Ltd, 2023)
Compressed air; Electric energy storage; Electric power transmission networks; Energy management; Hydrogen storage; Smart power grids; Energy; Energy demands; Energy storage applications; Energy storage system; Energy storage technologies; Micro grid; Renewable energies; Smart grid; Storage systems; Technologies and applications; Renewable energy resources